Makam Sayyid Husein bin Abu Bakar al-Aydarus: Jaringan Spiritual Usmani di Indonesia akhir abad ke-19 - FRIAL RAMADHAN SUPRATMAN (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2016)
This article investigates Indonesian history with transnational approach espe- cially in tracing social community of Indonesia in the context of globalization during nineteenth century. In this article, author focuses on holy tomb of ulama or saint (wali), Sayyid Husein bin Abu Bakar al-Aydarus, who died in the late eighteenth century and buried in Batavia. Although he died more than a century a go, his influence through tomb still can be sensed until now. In the nineteenth century, the tomb of Sayyid Husein bin Abu Bakar al-Aydarus became a symbolic mediator of Arab Hadrami communities in Batavia to build contact with the only Independence Muslim states, Ottoman state, after the decline of Mughal state in 1857. In the late nineteenth century, Hadrami communities requested donation from Ottoman sultan or Caliph to repair the tomb of Sayyid Husein bin Abu Bakar al-Aydarus. Upon this request, author concludes that in the middle of modernization and globalization, Ottoman government in Istanbul at that juncture was still concerned to preserve its spiritual network wiwth Indonesian Archipelago based on the Tradition of Islam (al-din).